Mapping Global Prevalence of Acinetobacter baumannii and Recent Vaccine Development to Tackle It - Chaoying Ma; Siobhán McClean (Vaccines, 2021)
Acinetobacter baumannii is a leading cause of nosocomial infections that severely threaten public health. The formidable adaptability and resistance of this opportunistic pathogen have hampered the development of antimicrobial therapies which consequently leads to very limited treatment options. We mapped the global prevalence of multidrug-resistant A. baumannii and showed that carbapenem-resistant A. baumannii is widespread throughout Asia and the Americas. Moreover, when antimicrobial resistance rates of Acinetobacter spp. exceed a threshold level, the proportion of A. baumannii isolates from clinical samples surges. Therefore, vaccines represent a realistic alternative strategy to tackle this pathogen. Research into anti-A. baumannii vaccines have enhanced in the past decade and multiple antigens have been investigated preclinically with varying results. This review summarises the current knowledge of virulence factors relating to A. baumannii–host interactions and its implication in vaccine design, with a view to understanding the current state of A. baumannii vaccine development and the direction of future efforts.